Microalgae and probiotic bacteria as biofloc inducers in a hyper-intensive Pacific white shrimp (Penaeus vannamei) culture - Jiménez-Ordaz,Francisco J. (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2021)
ABSTRACT Biofloc systems in Pacific white shrimp (Penaeus vannamei) culture generate floccules that remove wastes, and hence, biofloc formation is promoted for shrimp production. This study evaluated the induction of biofloc formation using microalgae and probiotic bacteria in hyper-intensive Pacific white shrimp culture. The experiment was performed for six weeks in tanks (28,000 L each) stocked 350 ind m−3 and weight of 1400 ± 30 mg. Three treatments were assessed: 1) with two diatoms: Grammatophora sp. and Navicula sp., 2) with Navicula sp., and 3) without diatoms. All treatments were added with Schizochytrium sp. and Lactobacillus fermentum TD19. The following parameters were monitored during culture: ammonium, nitrites, nitrates, environmental variables, floccules volume, microorganism presence, the bromatological composition of biofloc, and growth performance parameters of P. vannamei. Our results indicated that the three induced biofloc presented a similar volume (8.34 ± 4.8 mL L−1) and ammonium concentration (<1.0 mg L−1). Treatment 1 generated floccules with the highest concentration of ciliates, rotifers, nematodes, lactic acid bacteria, and the lowest concentration of Vibrio spp. (1.2×103 UFC mL−1), evidencing a significant difference in bromatological composition, with the highest protein and lipid values (28.12 ± 0.50 and 22.44 ± 0.80% biofloc dry weight, respectively) and the best feed conversion ratio (0.89). Based on these results, we suggest that Schizochytrium sp., L. fermentum, and two diatoms should be used to induce biofloc in a hyper-intensive culture of P. vannmaei in order to provide a supplementary nutritional intake, which can constitute an advantage to reduce commercial feed rations.